How to Treat Melanoma? The Current Status of Innovative Nanotechnological Strategies and the Role of Minimally Invasive Approaches like PTT and PDT - Joana Lopes; Cecília M. P. Rodrigues; Maria Manuela Gaspar; Catarina Pinto Reis (Pharmaceutics, 2022)
Melanoma is the most aggressive type of skin cancer, the incidence and mortality of which are increasing worldwide. Its extensive degree of heterogeneity has limited its response to existing therapies. For many years the therapeutic strategies were limited to surgery, radiotherapy, and chemotherapy. Fortunately, advances in knowledge have allowed the development of new therapeutic strategies. Despite the undoubted progress, alternative therapies are still under research. In this context, nanotechnology is also positioned as a strong and promising tool to develop nanosystems that act as drug carriers and/or light absorbents to potentially improve photothermal and photodynamic therapies outcomes. This review describes the latest advances in nanotechnology field in the treatment of melanoma from 2011 to 2022. The challenges in the translation of nanotechnology-based therapies to clinical applications are also discussed. To sum up, great progress has been made in the field of nanotechnology-based therapies, and our understanding in this field has greatly improved. Although few therapies based on nanoparticulate systems have advanced to clinical trials, it is expected that a large number will come into clinical use in the near future. With its high sensitivity, specificity, and multiplexed measurement capacity, it provides great opportunities to improve melanoma treatment, which will ultimately lead to enhanced patient survival rates.